Author Correction: Cathepsin g Degrades Both Glycosylated and Unglycosylated Regions of Lubricin, a Synovial Mucin - Shan Huang (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.